Estimation of small-scale fisheries production development trend in Nepal - Chaudhary, Arun Kumar; Bhandari, Dila Ram (NCC Journal, 2020)
Nepal is a landlocked country with enormous natural diversity ranges from the world's highest peak, Mt. Everest to the Tarai area. Nepalese aquaculture is still in its early stages, and fish production is still insufficient in comparison to global levels. Fish is a popular cuisine in Nepal, and it is enjoyed by people of all ages, genders, and religions. The total national fish production is currently 77,000 m.t., with 28 percent coming from catch fisheries and 72 percent from aquaculture. Aquaculture and open-water capture fisheries account for around 2% of agricultural gross domestic product; this little share of the fisheries sector is promising, with an annual growth rate of 8–9%. Total fisheries production in Nepal was reported at 81070 metric tons in 2018, according to the World Bank assortment of development indicators, compiled from officially recognized bases. Small-scale fishermen's catch production and secondary data in Nepal's Chitwan District, Bagmati Province, from 2010 to 2019. Regression estimates model and multivariate regression analysis of time series data, the Cobb-Douglas production function equation rational technique is applied. Changes in the number of fish caught have an impact on the home economics and spending. The length of the river, outboard engine power, and regional differences in area were found to have a positive impact on small-scale fishermen's catch production, whereas gasoline, schooling, and family dependents had a negative impact, though fishing gear, kerosene, and fishermen's age had no considerable impact.